(untitled) (Journal of Economic Research & Business Administration, 2021)
This article reflects one of the ongoing issues experienced by higher educational institutions – the formation of sustainable financial mechanisms to effectively influence the results of their activities as well as to promote their strategic development, and to transition to the global market. Along with this, insufficient funding in the Republic of Kazakhstan affects the material and technical bases of higher educational institutions, as well as the implementation of IT innovations within them. The formation of endowment funds could be a way to diversify educational institutions’ finance. Endowment funds funded by donations and are used by non-profit organizations for specific purposes, usually to fund significant educational, scientific, and community programs. The article contains an analysis of the existing endowment funds at educational institutions of the Republic of Kazakhstan as well as foreign models of endowment funds. The process of endowment funds’ formation and their effectiveness indicators are considered as well. In addition, the article provides an analysis of global practices in operations of endowment funds and their implementation to Kazakhstani conditions. Also, recommendations on the legislative regulation of endowment funds, tax benefits, and other preferences on building relationships with potential and future donors were provided in this article. As a result of analysing endowment funds’ activities of the Republic of Kazakhstan, a number of their effectivity factors were identified. Key words: endowment funds, financial mechanism, financing of higher educational institutions, fundraising, budgeting.